A case of primary cutaneous γδT cell lymphoma complicated with hemophagocytic lymphohistiocytosis - Junchi TANG; Xueyi HUANG; Wenyong ZHANG; Lin HE; Haitao HU; Bin YANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
We report a case of primary cutaneous γδT cell lymphoma complicated with hemophagocytic lymphohistiocytosis. A 33-year-old female presented with nodule on her left arm for 1 month and erythema on her both legs for a week. Physical examination revealed redness and swelling of the left upper arm with nodule sized 6.8 cm, accompanied with elevated skin temperature and tenderness. A sinus with yellow exudate was observed in the center of the lesion. There were more than 10 red nodular plaques in various sizes with unclear boundaries and tenderness around the ankles. Histology showed atypical lymphoid infiltrate in the dermis. Immunohistochemistry showed positive for CD3, CD5, CD8, Granzyme B, TIA-1, TCRγδ and Ki67(90%). Bone marrow aspiration showed abnormal maturation of granulocytes, erythroid hyperplasia and hemophagocytosis by reticular cells. TCRG gene rearrangement showed clonal amplification peak in the target band. PET-CT revealed multiple lymphadenopathy in her body. The diagnosis was primary cutaneous Gamma-Delta T-Cell lymphoma with hemophagocytic lymphohistiocytosis. After 2 weeks of CHOP+VP-16 combined with chemotherapy, patient's body temperature became normal, and the skin lesions gradually subsided. During the regular follow-up, the patient's symptoms recurred many times, and new skin lesions repeatedly developed, without significant improvement after the treatments with different chemotherapy. One year later, patient received hematopoietic stem cell transplantation, and her condition became stable. Currently the patient is still under follow-up.